Carbon monoxide in an extremely metal-poor galaxy - Yong Shi (Nature Portfolio, 2016)
Extremely metal-poor galaxies in the local universe are the best analogues to investigating the interstellar medium at a quasi-primitive environment in the early universe. Here, the authors detect CO emission in a galaxy at 7% solar metallicity, offering direct evidence for the presence of molecular gas.